1991
DOI: 10.1111/j.1365-2125.1991.tb03950.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of low doses of apomorphine on spatiotemporal contrast sensitivity in healthy volunteers: a double‐blind placebo‐ controlled study.

Abstract: 1. Apomorphine (1 and 5 micrograms kg‐1) and placebo were given to nine normal volunteers, using a Latin‐square design and double‐blind procedures. The visual perception of static and moving patterns (static and motion contrast sensitivity) was evaluated before and 15 min after the dose administration. 2. Apomorphine (1 and 5 micrograms kg‐1), as compared with placebo, led to a significant overall reduction of the visual perception of movement. This effect was dose‐related, and apomorphine (5 micrograms kg‐1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Thus, the results cannot be simply related to sedation and were probably a specific set of effects. In fact, we observed fundamental differences between the effects of MDZ and those related to normal ageing [26] or apomorphine administration [28].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, the results cannot be simply related to sedation and were probably a specific set of effects. In fact, we observed fundamental differences between the effects of MDZ and those related to normal ageing [26] or apomorphine administration [28].…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, colour vision in vertebrates mediated by the parvocellular pathway, is also assumed to be related to GABA A receptors [49]. By contrast, we previously demonstrated that apomorphine preferentially reduced sensitivity to moving patterns at low spatial frequencies [28]. This result might be interpreted as a preferential involvement of the dopaminergic system in magnocellular pathways, which have broad band characteristics, with high sensitivity to contrast and temporal modulation, and mediate motion perception and stereopsis [48].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…color perception, visual acuity, visual object, and space perception) remain unchanged. A decrease in contrast sensitivity was found after infusion of apomorphine in healthy volunteers [82,83], suggesting that overstimulation of retinal or cortical dopamine receptors may result in reduced lower-order visual perception. The absence of a positive effect on higher-order perceptual functions in PD patients with VH might be related to a dosing-or a ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced dopamine levels are found in early PD patients resulting in impaired prefrontal functioning [78][79][80] presumably due to frontal compensation [81]. With disease progression, the number of prefrontal D1-like receptors is reduced and prefrontal functioning deteriorates [80,[82][83][84].…”
Section: The Role Of Mono-amines In the Development Of Visual Hallucimentioning
confidence: 99%